Physical activity, health‐related quality of life, and adjuvant endocrine therapy–related symptoms in women with hormone receptor–positive breast cancer. Issue 17 (2nd July 2020) - Sheppard, Vanessa B.; Dash, Chiranjeev; Nomura, Sarah; Sutton, Arnethea L.; Franco, Robert Lee; Lucas, Alexander; Ross, Masey; Adams‐Campbell, Lucile
Abstract : Background: Physical activity (PA) is recommended for women with breast cancer (BC); however, data are sparse on the association of PA with quality of life (QOL) and patient‐reported symptoms for women on adjuvant endocrine therapy (AET). Methods: Women with hormone receptor–positive BC who were taking AET completed standardized surveys about their health‐related QOL, AET‐related symptoms, and levels of PA using validated measures. A Wald chi‐square test and an analysis of variance were used to assess associations with PA and independent variables. Generalized linear regression analyses assessed associations between PA, QOL, and AET‐related symptoms. Results: The analytic cohort included 485 Black and White women. Black race, a high body mass index (BMI), and being on aromatase inhibitors (vs tamoxifen) were associated with lower PA in a bivariate analysis. In a multivariate analysis, lower self‐reported PA was associated with a high BMI ( P  = .02) and chemotherapy uptake ( P  = .006). Better health‐related QOL ( P  = .01), less severe overall AET‐related symptoms ( P  = .02), and less severe gynecological symptoms ( P  = .03) were associated with increasing levels of moderate PA. Conclusions: Among women taking AET, moderate levels of PA may be associated with fewer medication‐related symptoms and overall better ratings of health‐related QOL. Because of the low levels of PA observed in the sample overall and particularly for Black women, identifying successful strategies to promote PA are needed. Abstract : Among women taking adjuvant endocrine therapy, moderate levels of physical activity may be associated with fewer medication‐related symptoms and overall better ratings of health‐related quality of life. Because of the low levels of physical activity observed in the sample overall and particularly for Black women, identifying successful strategies to promote physical activity are needed.